Lama Mencari Kerja di Indonesia dengan Menggunakan Analisis Survival - Maya Friska (Future Science, 2021)
Unemployment hurts society. During this period of unemployment, job seekers will use their savings/assets. As long as the unemployment period has not ended, job seekers will need more of these savings/assets to meet their needs. This study aims to determine the effect of job seekers based on gender, age, and education level on how long they can get a job in Indonesia. This study uses the National Labor Force Survey Panel data set (SAKERNAS PANEL 2017) through a survival analysis approach with Cox Proportional Hazard Regression. The results showed that unproductive age and higher education level would extend the length of time job seekers was looking for work.